2013
DOI: 10.1021/am400660f
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Sensitive Reversible Stress-Response of Shape Memory Natural Rubber

Abstract: We found that constrained shape memory natural rubber (SMNR) generates mechanical stress when exposed to solvent vapor. When the solvent vapor is removed, the material reprograms itself. This process is reversible and the stress answer is proportional to the solvent vapor concentration. Further, the stress answer is specific to the solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
65
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 21 publications
(31 reference statements)
3
65
0
1
Order By: Relevance
“…[ 24 ] This is most uncommon because a conventional polymer network expands under these conditions, pressing the clamps apart. [ 24 ] This is most uncommon because a conventional polymer network expands under these conditions, pressing the clamps apart.…”
mentioning
confidence: 99%
“…[ 24 ] This is most uncommon because a conventional polymer network expands under these conditions, pressing the clamps apart. [ 24 ] This is most uncommon because a conventional polymer network expands under these conditions, pressing the clamps apart.…”
mentioning
confidence: 99%
“…Recently, we reported on the solvent sensitive stress response and the environmental memory of SNMR. We found that constrained SMNR generates reversible mechanical stress when exposed to solvent vapor which is proportional to the solvent concentration . We could further show that constrained SMNR is capable of memorizing the chemical nature of a solvent vapor and its concentration within its microstructure measurable by irreversible stress‐answer .…”
Section: Introductionmentioning
confidence: 60%
“…Actually, they are capable of exceeding by far well‐established SMAs. Examples are diverse trigger options (heat, pH, chemicals, mechanical stress, UV/IR, electric/magnetic fields), tunable trigger temperatures, narrow trigger ranges, cold programmability, extremely large stored strains, multishape memory, shape memory‐assisted self‐healing, and even heating rate sensitivity . However, the trigger temperatures of most SMPs are considerably lower compared to those of SMAs, which are known for trigger temperatures of more than 700 °C .…”
Section: Introductionmentioning
confidence: 99%